Design thinking as a driver of fuel efficiency in motorcycle testing operations - Aris Risdiyanto; Aditya Tirta Pratama; Gembong Baskoro (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2027)
Design Thinking has proven to be beneficial for solving complex problems in engineering and the industrial sector, yet the method is still underutilized in large-scale manufacturing. This paper demonstrates how Design Thinking can be applied to a motorcycle unit testing process to optimize fuel usage, reduce test costs, and improve sustainability. The methodology follows the five distinctive stages of empathize, define, ideate, prototype, and test (Brown, 2009; Plattner, Meinel, & Leifer, 2010). Insights were gathered from operators and engineers regarding inefficiencies such as idling and procedural inconsistency. Prototypes focusing on testing sequences and fuel measurement were implemented and tested under production conditions. Results showed that average fuel consumption decreased from 318.5 ml to 200 ml per unit—a reduction of 37%. Beyond cost savings, Design Thinking fostered collaboration, creativity, and shared ownership. This study demonstrates that human-centered innovation can deliver tangible efficiency and sustainability outcomes in the industrial sector (IDEO, 2015; Stanford d.school, 2020).   Keywords: Design Thinking, fuel optimization, motorcycle manufacturing, industrial efficiency, sustainability